1980
DOI: 10.1111/j.1365-2125.1980.tb04834.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the pharmacodynamic profiles of nomifensine and amitriptyline in normal subjects.

Abstract: 1 Six healthy male volunteers participated in a double-blind placebo crossover comparison of the pharmacodynamic profiles of single oral doses of 75 mg nomifensine and 50 mg amitriptyline. 2 Nomifensine treatment did not influence salivary flow and did not significantly affect psychomotor performance (critical flicker fusion, pursuit rotor and reaction time): in addition nomifensine had no significant effect on subjective measurements of sedation and concentration. 3 By contrast, amitriptyline treatment signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1982
1982
1991
1991

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Of these, 14 did not involve any measures that could be considered memory tests. However, it is noteworthy that one paper reported improvement in test performance in association with amitriptyline (Kupietz and Balka, 1976), and one no effect (Elwan et al, 1976) and the remainder reported detrimental effects of the drug (Landauer et al, 1969;Seppala et al, 1975;Seppala, 1977;Bye et al, 1978;Crome and Newman, 1978;Chan et al, 1980;Scott et al, 1982;Culig et al, 1983;Hindmarch et al, 1983;Linnoila et al, 1983;Hanks, 1984;Burns et al, 1986). Of the fifteen studies including memory tests (see Table l), nine involved administration to healthy volunteers ranging from 25 mg to 75 mg, all but one as a single dose.…”
Section: Amitriptylinementioning
confidence: 99%
“…Of these, 14 did not involve any measures that could be considered memory tests. However, it is noteworthy that one paper reported improvement in test performance in association with amitriptyline (Kupietz and Balka, 1976), and one no effect (Elwan et al, 1976) and the remainder reported detrimental effects of the drug (Landauer et al, 1969;Seppala et al, 1975;Seppala, 1977;Bye et al, 1978;Crome and Newman, 1978;Chan et al, 1980;Scott et al, 1982;Culig et al, 1983;Hindmarch et al, 1983;Linnoila et al, 1983;Hanks, 1984;Burns et al, 1986). Of the fifteen studies including memory tests (see Table l), nine involved administration to healthy volunteers ranging from 25 mg to 75 mg, all but one as a single dose.…”
Section: Amitriptylinementioning
confidence: 99%
“…In a second study, the same investigators noted adverse effects of this drug on measures of vigilance, on the digit symbol substitution, tapping rate and subjective ratings of mood 2 hours after the ingestion of 12-5 mg and 25 mg single doses. Depressed critical flicker fusion, prolonged reaction times and deficits on the pursuit rotor test were recorded by Chan et al (1980) 2,4 and 6 hours after a single 50 mg dose of amitriptyline. Similar reports of performance deficits had been recorded earlier by Crome & Newman (1978) 4 and 6 hours after a 25 mg dose, and by Peck et al (1979) up to 5 hours after a 25 mg dose.…”
Section: Amitriptylinementioning
confidence: 99%
“…In the last two studies outlined above it is important to note that nomifensine had no effects on several measures of cognitive and motor performance. In a recent study (Chan et al 1980) a single dose of nomifensine (75 mg) was administered to healthy volunteers in a cross-over design with amitriptyline and placebo. Nomifensine had no significant effect on measures of choice reaction time, critical flicker fusion, pursuit rotor and rating scales of mood, 2, 4, and 6 hours following administration.…”
Section: Nomifensinementioning
confidence: 99%